2018
DOI: 10.1371/journal.pbio.2006906
|View full text |Cite
|
Sign up to set email alerts
|

Should police have access to genetic genealogy databases? Capturing the Golden State Killer and other criminals using a controversial new forensic technique

Abstract: On April 24, 2018, a suspect in California’s notorious Golden State Killer cases was arrested after decades of eluding the police. Using a novel forensic approach, investigators identified the suspect by first identifying his relatives using a free, online genetic database populated by individuals researching their family trees. In the wake of the case, media outlets reported privacy concerns with police access to personal genetic data generated by or shared with genealogy services. Recent data from 1,587 surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 8 publications
(12 reference statements)
0
85
0
1
Order By: Relevance
“…In the aftermath of the Golden State Killer criminal case, a survey of 1587 US residents found that the majority of respondents supported police searches of genetic websites that identify genetic relatives (79%) and the disclosure of direct-to-consumer genetic testing customer information to the police (62%), as well as the creation of fake profiles of individuals by the police on genealogy websites (65%). However, respondents were significantly more supportive of these activities to identify perpetrators of violent crimes, perpetrators of crimes against children and missing persons cases (Guerrini, Robinson, Petersen, & McGuire, 2018).…”
Section: Long-range Familial Searches In Recreational Dna Databasesmentioning
confidence: 95%
“…In the aftermath of the Golden State Killer criminal case, a survey of 1587 US residents found that the majority of respondents supported police searches of genetic websites that identify genetic relatives (79%) and the disclosure of direct-to-consumer genetic testing customer information to the police (62%), as well as the creation of fake profiles of individuals by the police on genealogy websites (65%). However, respondents were significantly more supportive of these activities to identify perpetrators of violent crimes, perpetrators of crimes against children and missing persons cases (Guerrini, Robinson, Petersen, & McGuire, 2018).…”
Section: Long-range Familial Searches In Recreational Dna Databasesmentioning
confidence: 95%
“…Introduction Databases of whole genome-scale genotypes are becoming available in public (e.g., the UK Biobank [33]) or private (e.g., from direct-to-consumer genetic testing providers [34], such as 23andMe [35]) databases. One of the straightforward applications for these data is to identify relatives, in particular distant relatives, which has not only been useful for ancestry and genealogy analysis by academic researchers, citizen scientists and individual consumers [34], but also has strong implications for forensics (a great example is the arrest of the alleged Golden State serial killer in California using genetic genealogy methods [36]). Table 5 Statistical tests on AUCs using DeLong's Test, showing that there is no statistical difference among the top four teams in the previous table at a significance level of 0.01 for both cutoff thresholds (1E-2 for the triangle above the main diagonal of the matrices, and 1E-5 for the triangle below the main diagonal of the matrices) for converting the outputs of semi-parallel GWAS (estimated probabilities) to binary labels (for AUC computation) Many algorithms have been developed for kin relationship inference from genotype data.…”
Section: Track 3: Secure Search Of Dna Segments In Large Genome Databmentioning
confidence: 99%
“…OpenSNP collects phenotypic information, while GEDmatch is focused on reconstructing genealogies, and users who have shared their genetic information can also access the genetic information from other users. The possibility of re-identification via these services grabbed international headlines recently with the arrest of the Golden State Killer by criminal investigators (Guerrini et al 2018). In general, public and private databases are biased towards genomes of Europeandescent (Ram et al 2018), and recent work suggests that in the near future, re-identification of individuals of European ancestry in the US who have publicly released their genetic information is likely (Erlich et al 2018).…”
Section: Evolving Privacy Concernsmentioning
confidence: 99%